Application of whole-genome sequencing for distinguishing relapse from reinfection in tuberculosis patients from Lithuania - Vasiliauskaitė, Laima; Zinola, Alma; Marco, Federico Di; Davidavičienė, Valerija Edita; Nakčerienė, Birutė; Vaitulionytė, Agnė; Cirillo, Daniela Maria; Kačergius, Tomas (International journal of infectious diseases, 2026)
•Reinfection accounted for 40% of recurrent tuberculosis (TB) cases.•Half of the TB treatment failures were found to be reinfections.•Only 55% of patients were correctly differentiated as relapse or treatment failure.•Extensively drug-resistant TB emerged undetected due to limited diagnostics. Tuberculosis (TB) can reoccur even after successful treatment due to endogenous reactivation or exogenous reinfection. Understanding the aetiology of TB recurrence might prevent further transmission and development of resistance. Therefore, this study aimed to assess the rate of true TB relapses versus reinfection among patients with TB recurrence in Lithuania using whole-genome sequencing (WGS). This study included 62 Mycobacterium tuberculosis complex (MTBC) strains recovered from 29 pulmonary TB patients who had at least one reported TB recurrence or treatment failure episode between 2016 and 2023. To investigate potential sources of transmission in reinfected patients, 4 additional MTBC sequences were included in the analysis. The analysis of WGS results was performed using an in-house bioinformatic pipeline. A cut-off of 5 single nucleotide polymorphisms was used to differentiate between relapse and reinfection. Majority (60%) of all recurrent TB cases were caused by true relapse, while reinfections with a different strain accounted for 40%. Moreover, half of the treatment failures were also found to be reinfections. The risk of reinfection is underestimated in Lithuania, highlighting the need for rapid changes in diagnostics and infection control strategies to contain the transmission of extensively drug-resistant TB (XDR-TB) strains in Lithuania.